On the socio-cognitive coercion mechanism of the formation of mandarin construction “V+ta(he)+XP” - Zhang, Pan (Frontiers in Psychology, 2025)
This study employs a cognitive-sociolinguistic framework to investigate the formation mechanism of the Mandarin single-object construction “V+Ta+XP” and the grammaticalization of the non-referential pronoun “Ta.” Building on the hypothesis that “Ta” originates from the abbreviation of the expletive phrase “Ta x de,” we conduct a comparative analysis of the syntactic, pragmatic, and socio-cognitive features of the “V+Ta+XP” construction and its precursor “V+Ta x de+XP” structure. Drawing on 402 “V+Ta x de+XP” and 607 “V+Ta+XP” instances extracted from the CCL and BCC corpora, our findings reveal systematic parallels in syntactic configurations and pragmatic functions, alongside critical socio-cognitive divergences. Specifically, the “V+Ta+XP” construction emerges as a de-vulgarized variant of “V+Ta x de+XP,” driven by socio-cognitive coercion—a process that suppresses vulgar components “x de” to mitigate face-threatening effects while preserving syntactic integrity and emotional salience. By integrating construction grammar, politeness theory, and sociolinguistic variation, this study demonstrates how social norms (e.g., register formality, gender dynamics) and cognitive-emotional needs jointly shape grammaticalization. The proposed framework advances coercion theory by highlighting the interplay of linguistic structure, pragmatic adaptation, and socio-cultural constraints, offering novel insights into the evolution of non-referential elements in Mandarin and their role in balancing expressive force with social acceptability.